THE CALCULATION OF TEMPERATURE FIELDS DURING VULCANIZATION OF ELASTOMER PRODUCTS - Ishchenko, V. O.; Shaptala, M. V. (Science and Transport Progress, 2005)
A procedure has been developed of calculating a 3-D temperature field with application of FEM for determination of vulcanization time of elastomer products with geometrically complex heating surfaces. On the example of heavy-duty tire it has been shown that the account of the 3-D nature of temperature distribution allows to reduce vulcanization time by 6–8 % in comparison with the plane section procedure, which is currently used in industry, which results in significant savings of thermal energy in conditions of commercial production.